Ultra-high oxidation resistance of nano-structured thin films. (March 2021) - Aschauer, E.; Wojcik, T.; Polcik, P.; Hunold, O.; Arndt, M.; Dalbauer, V.; Mayrhofer, P.H.; Felfer, P.; Riedl, H.
Abstract: Diffusion driven high-temperature oxidation is one of the most important failure mechanisms of protective thin films in industrial applications. Within this study, we investigated the diffusion of oxygen at 800 to 1100 °C through nano-laminated crystalline Ti-Al-N and amorphous Mo-Si-B based multilayer coatings. The most prominent oxygen diffusion pathways, and hence the weakest points for oxidation, were identified by combining 18 O tracer diffusion and atom probe tomography. An oxygen inward diffusion along column boundaries within Ti-Al-N layers in front of a visually prevalent oxidation front could be proven, highlighting the importance of these fast diffusion pathways. Furthermore, the amorphous Mo-Si-B layers act as barriers and therefore mitigate the migration of oxygen by accumulating reactive O species at a nanoscale range. Preventing oxygen diffusion along column boundaries – through the implementation of amorphous interlayers – lead to paralinear oxidation behavior and stable scales even after 7 h at 1100 °C. Our results provide a detailed insight on the importance of morphological features such as grain and column boundaries during high-temperature oxidation of protective thin films, in addition to their chemistry. Graphical abstract: Unlabelled Image Highlights: Ultra high oxidation resistance Blocking fast diffusion pathways through amorphous interlayers 18 O tracer diffusion for highly resolved diffusion pathway analysis using atom probe tomography Identification of fast diffusion pathways in fcc-(Ti, Al)N protective coatings Atom probe tomography of nano-scaled (Ti, Al)N/Mo-Si-B multilayer coating.